Manifestation of theme as a point of departure in the result and discussion section of academic research articles - Ebrahimi, Seyed Foad; Chan, Swee Heng (Universiti Putra Malaysia Press, 2013)
Theme is the element which serves as the point of departure of the message in a clause. It plays a major role in text organization, enabling a text to be communicated and understood clearly (Halliday, 1994). One issue in research article writing is how the writer deals with this important textual feature. This study did an analysis of theme types used in result and discussion section of research articles using Halliday's (2004) model of thematic organization. The study was carried out on the corpus of 16 result and discussion sections that were sourced from 16 research articles published in UPM journals in 2010 and 2011 from four disciplines, which are English Language Teaching, Economics, Biology, and Civil Engineering (4 from each discipline). The results revealed disciplinary differences in the use of theme across the four disciplines. These differences are supported by the claim that writing in each discipline is shaped by the discipline's own rules and conventions (Hyland, 2009; North, 2005). The results also supported the idea proposed by Gosden (1992) that theme types are important in fulfilling rhetorical functions of research article sections.